RESPONSE OF MAIZE TO TILLAGE AND NITROGEN MANAGEMENT - A. Wasaya; M. Tahir; A. Tanveer; M. Yaseen (Journal of Animal and Plant Sciences, 2012)
Best nitrogen management practices are the pre-requisite to warrant high maize yield. Thus, experiments were conducted to study the “effect of tillage and split application of nitrogen on hybrid maize” under semi-arid conditions of Pakistan, during fall 2008 and 2009. The experiments were laid out in randomized complete block design with split-plot arrangement, replicated three times in a net plot size of 4.5m x 10m at the Agronomic Research Area, University of Agriculture, Faisalabad.Three tillage treatments (conventional tillage (2-cultivation), tillage with mouldboard plough + 2-cultivation and tillage with chisel plough + 2-cultivation) were kept in main plots, while nitrogen application at different growth stages (Whole at sowing, ½ at sowing + ½ at V5 (5-leaf stage), ½ at sowing + ½ at tasseling, ½ at V5 + ½ at tasseling, 1/3 at sowing + 1/3 at V5 + 1/3 at tasseling)  in sub-plots. Tillage methods improved the plant height, biomass yield, harvest index and shelling percentage during both the years while nitrogen application had no effect on plant height and harvest index but had significant effect on shelling percentage and biomass yield of maize. Chisel ploughed plots produced tallest plants, higher biomass, harvest index and shelling percentage while mould board plough resulted to shortest plants, lower biomass, harvest index and shelling percentage during both the years. Nitrogen application in three splits produced highest biomass yield and shelling percentage during 2008 and 2009. Variation in biomass yield in maize suggested temporal nitrogen management practices in maize grown by ploughing the soil with chisel plough followed by cultivator under semi-arid climatic conditions.
Keywords: Tillage; Maize; Harvest Index; Shelling Percentage; Biomass yield